Effect of Mixed Nuts on Body Weight and Composition, and Gut Microbiome (P08-054-19). (24th October 2019) - Woo, Shih Lung; Ben-Nissan, Dina; Ezzat-Zadeh, Zahra; Yang, Jieping; Zhang, Lijun; Lee, Rupo; Gilbuena, Irene; Thames, Gail; Rasmusen, Anna; Henning, Susanne; Heber, David; Li, Zhaoping
Abstract: Objectives: This study was designed to assess the effects of mixed nut consumption on body weight and composition, and gut microbiome in obese individuals. Primary outcome was change in body weight and composition. Secondary outcomes include gut microbiome composition, inflammatory markers, and plasma lipids. Methods: The reported results are from an interim analysis ( n  = 50) of a randomized, placebo controlled, parallel study. Total enrollment target is 154 overweight/obese subjects (BMI 27–35 kg/m 2 ). Participants were randomly assigned to consume either 1.5oz mixed tree nuts or pretzels with equal calorie content daily for 24 weeks. The study included a 12-week weight loss phase (500 kcal per day less than total daily energy expenditure), followed by a 12-week weight maintenance phase. Body composition, fasting blood, and stool samples were collected at baseline, week 12 and 24. Body composition, and vitals were analyzed, whereas plasma lipid profile, fecal microbiome, and microbiome metabolites analysis is still pending. Results: At week 12, subjects from both the pretzel ( n  = 15, 10 dropouts; P  = 0.009) and nut group ( n  = 22, 3 dropouts; P  = 0.038) lost significant amount of weight. The trend of weight changes did not differ between groups ( P  = 0.530). Subjects from both groups were able to sustain weight loss through 24 weeks (pretzel: 81.43 ± 3.85 kg at baseline vs. 79.43 ± 4.08 kg at week 24, P  = 0.028; nut: 84.26 ± 3.78 kg at baseline vs. 82.38 ± 3.72 kg at week 24, P  = 0.026). At week 12, fat mass in both groups was significantly decreased (pretzel: P  = 0.002; nut: P  = 0.012). The trend of fat changes did not differ between groups ( P  = 0.547). Subjects from both groups were able to sustain fat loss through 24 weeks (pretzel: 30.84 ± 1.75 kg at baseline vs. 29.25 ± 2.12 kg at week 24, P  = 0.024; nut: 31.51 ± 1.56 kg vs 30.21 ± 1.81 kg at week 24, P  = 0.04). Muscle mass, and blood pressure were not significantly different between both groups. Conclusions: Our data suggested that tree nuts could be consumed as part of a healthy weight loss meal plan without concern of causing weight gain. Further analysis of the remaining samples is needed to confirm results. Due to higher dropouts in the pretzel group, future intention-to-treat analysis is also needed to eliminate bias. Funding Sources: This study is supported by the International Tree Nut Council.